Preparation method of high-toughness halogen-free flame-retardant composite material

By staggered stacking of high-toughness prepregs and halogen-free flame retardant adhesive films, the problem of difficult to prepare high-toughness and high flame retardant composite materials in the prior art is solved, and the high toughness and high flame retardant performance of the material are achieved.

CN119773106APending Publication Date: 2025-04-08AVIC BEIJING AERONAUTICAL MFG TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840562.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult to prepare prepreg composite materials that have both high toughness and high flame retardancy.

Method used

By preparing high-toughness prepregs and halogen-free flame retardant films, they are staggered and laid on the laying mold and cured to form a high-toughness halogen-free flame retardant composite material.

Benefits of technology

The high toughness and high flame retardant properties of composite materials are achieved, and the internal bonding strength and structural strength of the material are improved, while avoiding the poor processability problems caused by excessive addition of toughening agents and flame retardants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119773106A_ABST
    Figure CN119773106A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-toughness halogen-free flame-retardant composite material, which comprises the following steps: preparing a thermoplastic resin glue solution, dragging a reinforcing material to be immersed in the thermoplastic resin glue solution by a prepreg, drying, and cooling to obtain a high-toughness prepreg, the mass content of thermoplastic resin in the high-toughness prepreg being 25-80%; halogen-free flame retardant adhesive is prepared, the halogen-free flame retardant adhesive is molded into a halogen-free flame retardant adhesive film through a hot melting method, and the mass content of a halogen-free flame retardant in the halogen-free flame retardant adhesive film is 30%-80%; laying a high-toughness prepreg and a halogen-free flame-retardant adhesive film on the laying mold to obtain a high-toughness halogen-free flame-retardant preform; and curing and forming a high-toughness halogen-free flame-retardant preform to obtain the high-toughness halogen-free flame-retardant composite material. The preparation method provided by the invention can realize the preparation of the composite material with both high toughness and high flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and more specifically to a method for preparing a high-toughness halogen-free flame-retardant composite material. Background Art

[0002] Resin-based composite materials are widely used in aerospace and automobile manufacturing fields due to their many advantages such as high strength, high modulus, high temperature resistance, fatigue resistance, and strong designability.

[0003] However, conventional resin-based composite materials are relatively brittle. When they encounter impacts such as hail and gravel, their comprehensive performance decays greatly. At the same time, resin-based composite materials generally have poor flame retardancy. When used as aircraft cabin and automotive decorative materials, they often fail to meet the requirements for flame retardancy. At present, the method for improving the toughness of resin-based composite materials is usually to add toughening agents such as thermoplastic resins or rubbers to the resin matrix, and the amount of addition is also limited. The method for improving the flame retardancy of resin-based composite materials is usually to add flame retardants to the resin matrix. When too little toughening agent is added to the resin matrix, the toughening effect cannot be achieved. When too much toughening agent is added, the resin system will become sticky, the stirring equipment will be limited, and the mixing will be uneven. At the same time, the viscous resin system cannot be mixed with flame retardants to improve the flame retardancy of the resin-based composite material. Excessive addition of toughening agents and flame retardants will also lead to the disadvantage of poor processability of prepreg preparation.

[0004] Therefore, due to the limitation of the prepreg preparation process, the conventional method of adding toughening agent and flame retardant to the resin matrix at the same time to improve the toughness and flame retardancy of the resin-based composite material has a limited amount of additives added, and therefore, the requirements of the composite material for high toughness and flame retardancy cannot be met. It is difficult to prepare a prepreg composite material with both high toughness and high flame retardancy in the prior art. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The technical problem to be solved by the present invention is that it is difficult to prepare a prepreg composite material having both high toughness and high flame retardancy in the prior art.

[0007] (II) Technical solution

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] The present invention provides a method for preparing a high-toughness halogen-free flame-retardant composite material, comprising the following steps:

[0010] Prepare a thermoplastic resin adhesive, use a prepreg machine to pull the reinforcing material into the thermoplastic resin adhesive, and obtain a high-toughness prepreg after drying and cooling, wherein the mass content of the thermoplastic resin in the high-toughness prepreg is 25% to 80%;

[0011] Prepare a halogen-free flame retardant adhesive, and shape the halogen-free flame retardant adhesive into a halogen-free flame retardant adhesive film by a hot melt method, wherein the mass content of the halogen-free flame retardant in the halogen-free flame retardant adhesive film is 30% to 80%;

[0012] Laying the high-toughness prepreg and the halogen-free flame-retardant adhesive film on a laying mold to obtain a high-toughness halogen-free flame-retardant preform;

[0013] The high-toughness halogen-free flame-retardant preform is cured and formed to obtain a high-toughness halogen-free flame-retardant composite material.

[0014] Preferably, the multiple layers of the high-toughness prepreg and the multiple layers of the halogen-free flame-retardant adhesive film are alternately stacked in the thickness direction.

[0015] Preferably, one or more layers of the halogen-free flame-retardant adhesive film are provided between two adjacent layers of the high-toughness prepreg;

[0016] Preferably, one or more layers of the high-toughness prepreg are disposed between two adjacent layers of the halogen-free flame-retardant adhesive film.

[0017] Preferably, the thermoplastic resin glue comprises the following components by mass fraction:

[0018] Thermoplastic resin, 25% to 80%;

[0019] Epoxy resin, 10% to 75%;

[0020] Curing agent, 2% to 80%;

[0021] Curing accelerator, 0-50%.

[0022] Preferably, the thermoplastic resin includes at least one of polysulfone, polyarylethernitrile, polyaryletherketone, polyetheretherketone, thermoplastic polyimide, polyethersulfone, and polycarbonate.

[0023] Preferably, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin;

[0024] And / or, the curing agent includes at least one of aliphatic amine curing agents, aromatic amine curing agents, acid anhydrides, imidazoles, and polyamides;

[0025] And / or, the curing accelerator includes at least one of a substituted urea curing accelerator, a boron trifluoride amine complex curing accelerator, a triphenylphosphine and its salt curing accelerator, and a tertiary amine and its salt curing accelerator.

[0026] Preferably, the reinforcing material includes at least one of carbon fiber and its fabric, glass fiber and its fabric, aramid fiber and its fabric, basalt fiber and its fabric, and aramid fiber and its fabric.

[0027] Preferably, the halogen-free flame retardant glue comprises the following components by mass fraction:

[0028] Halogen-free flame retardant, 30% to 80%;

[0029] Epoxy resin, 20% to 70%;

[0030] Curing agent, 2% to 80%;

[0031] Curing accelerator, 0-50%;

[0032] The type of the curing agent in the halogen-free flame retardant glue is consistent with the type of the curing agent in the thermoplastic resin glue solution, and the type of the curing agent accelerator in the halogen-free flame retardant glue is consistent with the type of the curing agent accelerator in the thermoplastic resin glue solution.

[0033] Preferably, the halogen-free flame retardant includes at least one of a phosphorus-based flame retardant, a nitrogen-based flame retardant, a silicon-based flame retardant, and an inorganic metal compound flame retardant.

[0034] Preferably, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin;

[0035] And / or, the curing agent includes at least one of aliphatic amine curing agents, aromatic amine curing agents, acid anhydrides, imidazoles, and polyamides;

[0036] And / or, the curing accelerator includes at least one of a substituted urea curing accelerator, a boron trifluoride amine complex curing accelerator, a triphenylphosphine and its salt curing accelerator, and a tertiary amine and its salt curing accelerator.

[0037] (III) Beneficial effects

[0038] The above technical solution of the present invention has at least the following advantages:

[0039] 1. The high-toughness halogen-free flame-retardant composite material prepared by the preparation method of the high-toughness halogen-free flame-retardant composite material provided by the present invention has both high material toughness and high flame retardant performance, and can meet the application requirements in its specific field.

[0040] 2. Compared with the conventional preparation method of prepreg composite materials in the prior art, the present application stacks a high-toughness prepreg with a halogen-free flame-retardant adhesive film with high flame retardant properties, and finally solidifies and forms them into a high-toughness halogen-free flame retardant composite material, so that the composite material has high toughness and high flame retardant properties. At the same time, during the curing process, the adhesive film is heated and melted, and can penetrate into the prepreg on both sides, so that the bonding strength between the thermoplastic resin on the adhesive film and the additive material in the prepreg is higher, which can improve the internal bonding strength of the composite material, and then improve the structural strength of the corresponding composite material parts.

[0041] 3. In the present invention, the number of stacking layers of high-toughness prepreg and halogen-free flame-retardant film can be set according to the performance requirements of the final composite material. Under the premise of a certain thickness of the composite material, when the prepared composite material requires higher toughness, the number of stacking layers of high-toughness prepreg can be increased, and when the prepared composite material requires higher flame retardant performance, the number of stacking layers of halogen-free flame-retardant film can be increased. Therefore, the method provided by the present invention has strong designability in the preparation process.

[0042] 4. In the present invention, no flame retardant is added to the prepared high-toughness prepreg or a small amount of flame retardant is added, so that the molding of the high-toughness prepreg can be achieved. At the same time, the prepared high-toughness prepreg has a high viscosity, which can be easily positioned during stacking. No toughening agent is added to the prepared halogen-free flame retardant film, and there will be no problem of not being able to add flame retardants to the system due to excessive addition of toughening agent, so the preparation of halogen-free flame retardant film with high flame retardant performance can be achieved. Finally, by curing the combination of halogen-free flame retardant film and high-toughness prepreg, the preparation of high-toughness halogen-free flame retardant composite materials can be achieved, so that the composite material has both high toughness and high flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 It is a schematic flow chart of a method for preparing a high-toughness halogen-free flame-retardant composite material provided by an embodiment of the present invention.

[0045] Figure 2 It is a process flow chart of preparing the high-toughness prepreg provided by an embodiment of the present invention.

[0046] Figure 3 The present invention provides a halogen-free flame retardant film preparation process flow chart. DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0048] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly located on the other element or indirectly located on the other element. When an element is referred to as being "connected to" another element, it may be directly connected to the other element or indirectly connected to the other element.

[0049] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention, and do not indicate that a device or element must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.

[0050] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating relative importance or indicating the number of technical features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The specific implementation of the present invention is described in more detail below in conjunction with specific embodiments:

[0051] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a high-toughness halogen-free flame-retardant composite material, comprising the following steps:

[0052] S1. Prepare thermoplastic resin adhesive, pull the reinforcing material into the thermoplastic resin adhesive through a prepreg machine, and obtain a high-toughness prepreg after drying and cooling, wherein the mass content of the thermoplastic resin in the high-toughness prepreg is 25% to 80%; wherein the reinforcing material includes at least one of carbon fiber and its fabric, glass fiber and its fabric, aramid fiber and its fabric, basalt fiber and its fabric, and aramid fiber and its fabric. Furthermore, when preparing high-toughness prepregs, the reinforcing material is kept immersed in the thermoplastic resin adhesive for a certain period of time (the immersion time is determined according to the measured prepreg surface weight) so that the resin content in the prepared high-toughness prepreg reaches the required requirements, and the oven temperature is set according to the solvent used, such as: when acetone is used as the solvent, the oven temperature is 50-80°C; when ethyl acetate is used as the solvent, the oven temperature is 80-100°C; when 1,2-dichloroethane is used as the solvent, the oven temperature is 80-120°C; when dichloromethane is used as the solvent, the oven temperature is 30-80°C; when N,N-dimethylformamide is used as the solvent, the oven temperature is 140-160°C. The prepreg preparation rate is 1-10 m / min. More specifically, the following can be used: Figure 2 The process flow shown is used to prepare high-toughness prepreg. The specific preparation process is as follows: first, the additive material is woven through a yarn rack device, and the woven additive material is unwound through a reinforcing material unwinding device, and then pulled through a prepreg machine, so that the additive material passes through a glue tank containing a thermoplastic resin glue, and the pulling speed of the prepreg machine is controlled so that the reinforcing material is immersed in the thermoplastic resin glue in the glue tank for a certain period of time. Then the reinforcing material with the thermoplastic resin glue is pulled through a high-temperature blast drying oven, and the hot air blown out of the high-temperature blast drying oven dries the reinforcing material with the thermoplastic resin glue. After drying, the high-toughness prepreg is formed through the upper hot pressing roller and the lower hot pressing roller, and the isolation film is laid through the isolation film unwinding system, and the release paper is laid through the release paper unwinding system, and then pulled through the cooling plate to achieve the shaping of the high-toughness prepreg, and finally passed through the upper extrusion roller and the lower extrusion roller, and wound by the winding system to achieve the preparation and winding of the high-toughness prepreg.

[0053] S2. preparing a halogen-free flame retardant adhesive, and molding the halogen-free flame retardant adhesive into a halogen-free flame retardant adhesive film by a hot melt method, wherein the mass content of the halogen-free flame retardant in the halogen-free flame retardant adhesive film is 30% to 80%;

[0054] S3. Lay high-toughness prepreg and halogen-free flame-retardant adhesive film on the paving mold to obtain a high-toughness halogen-free flame-retardant preform; specifically, before paving, the high-toughness prepreg and the halogen-free flame-retardant adhesive film should be cut into the same size, and the halogen-free flame-retardant adhesive film should be slightly pressurized and heated after being laid on the high-toughness prepreg to facilitate the peeling of the release paper material without damaging the adhesive film material, and then continue to lay. Specifically, the following method can be used: Figure 3The process flow shown is used to prepare halogen-free flame retardant adhesive film. The specific preparation process is as follows: first, the halogen-free flame retardant adhesive is placed between the two rubber rollers of the hot melt film making machine, and then the release paper on the release paper unwinding system is pulled to move in the production direction, and at the same time, the rubber roller is controlled to coat the halogen-free flame retardant adhesive on the release paper, and the thickness of the adhesive coating is controlled by the rubber roller. The thickness of the adhesive coating is then detected by a thickness gauge, and adjusted in real time. Then, the release paper coated with the halogen-free flame retardant adhesive is pulled through a cooling plate to achieve cooling and shaping of the halogen-free flame retardant adhesive film. Finally, the isolation film is placed through the isolation film unwinding system and reeled through the reeling system to achieve the preparation and reeling of the halogen-free flame retardant adhesive film.

[0055] S4, curing and molding a high-toughness halogen-free flame-retardant preform to obtain a high-toughness halogen-free flame-retardant composite material. Specifically, the curing and molding can be vacuum-assisted oven curing and molding or autoclave hot pressing curing and molding. The specific curing and molding method can be determined according to actual use requirements.

[0056] In one embodiment, multiple layers of high-toughness prepreg and multiple layers of halogen-free flame-retardant adhesive films are alternately stacked in the thickness direction.

[0057] In one embodiment, one or more layers of halogen-free flame retardant adhesive film are provided between two adjacent layers of high-toughness prepreg;

[0058] In one embodiment, one or more layers of high-toughness prepreg are disposed between two adjacent layers of halogen-free flame-retardant adhesive films.

[0059] In one embodiment, the thermoplastic resin glue comprises the following components by mass fraction:

[0060] Thermoplastic resin, 25% to 80%; epoxy resin, 10% to 75%; curing agent, 2% to 80%; curing accelerator, 0 to 50%. Furthermore, the corresponding curing agent and curing accelerator can be added in a targeted manner according to the specific materials selected for the thermoplastic resin and epoxy resin. Whether to add the corresponding solvent can be determined according to the mixed viscosity of the thermoplastic resin glue required for the final molding. The selection of the solvent needs to consider whether the material can be completely dissolved in the solvent, and at the temperature of further solvent removal, the system does not undergo a curing reaction in a short time.

[0061] The thermoplastic resin includes at least one of polysulfone, polyarylethernitrile, polyaryletherketone, polyetheretherketone, thermoplastic polyimide, polyethersulfone, and polycarbonate. The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin; the curing agent includes at least one of aliphatic amine curing agent, aromatic amine curing agent, acid anhydride, imidazole, and polyamide; the curing accelerator includes at least one of substituted urea curing accelerator, boron trifluoride amine complex curing accelerator, triphenylphosphine and its salt curing accelerator, and tertiary amine and its salt curing accelerator.

[0062] In one embodiment, the halogen-free flame retardant adhesive comprises the following components by mass fraction:

[0063] Halogen-free flame retardant, 30% to 80%; epoxy resin, 20% to 70%; curing agent, 2% to 80%; curing accelerator, 0 to 50%. Furthermore, the corresponding curing agent and curing accelerator can be added in a targeted manner according to the specific materials selected for the epoxy resin. Among them, when the curing agent and curing accelerator are added to both the thermoplastic resin glue and the halogen-free flame retardant glue, the type of curing agent in the halogen-free flame retardant glue is consistent with the type of curing agent in the thermoplastic resin glue, and the type of curing agent accelerator in the halogen-free flame retardant glue is consistent with the type of curing agent accelerator in the thermoplastic resin glue. So that after stacking the high-toughness prepreg and the halogen-free flame retardant adhesive film, each layer of the composite material can maintain the same curing rate during the curing molding process.

[0064] Among them, the halogen-free flame retardant includes at least one of phosphorus-based flame retardants (such as ammonium polyphosphate, phosphates and polyphosphates, phosphate esters, organic hypophosphorous acid, etc.), nitrogen-based flame retardants (such as melamine, guanidine salts, melamine cyanurate, etc.), silicon-based flame retardants (such as silicon dioxide, polysiloxane, etc.), and inorganic metal compound flame retardants (such as zinc borate, aluminum hydroxide, magnesium hydroxide, etc.). The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin; the curing agent includes at least one of aliphatic amine curing agent, aromatic amine curing agent, acid anhydride, imidazole, and polyamide; the curing accelerator includes at least one of substituted urea curing accelerator, boron trifluoride amine complex curing accelerator, triphenylphosphine and its salt curing accelerator, and tertiary amine and its salt curing accelerator. Specifically, when preparing halogen-free flame retardant adhesive, the types of curing agent and curing accelerator should be the same as those used to prepare thermoplastic resin adhesive, so that after stacking high-toughness prepreg and halogen-free flame retardant adhesive film, each layer of the composite material can maintain the same curing rate during the curing molding process.

[0065] The following are specific embodiments provided in this application:

[0066] Example 1

[0067] Preparation of thermoplastic resin glue: 5 kg of epoxy resin E-51, 5 kg of epoxy resin AG-80, 20 kg of poly (arylene ether nitrile) (PEEN) and 1.5 kg of dicyandiamide were dissolved in N, N-dimethylformamide solvent at room temperature and mixed evenly, and the resin mass concentration was diluted to 50% by adding N, N-dimethylformamide solvent to obtain thermoplastic resin glue;

[0068] The thermoplastic resin glue obtained in the previous step is placed in the glue tank of the prepreg system. Carbon fiber is selected as the reinforcing material. The T700 carbon fiber with a pre-calculated number of axes is passed through the creel device. The prepreg machine pulls the T700 carbon fiber through the above thermoplastic resin glue at a certain pulling rate, so that the resin content of the obtained prepreg is 33%, and is dried in a high-temperature blast drying oven at 145°C to remove the solvent, hot-pressed by a hot pressing roller at 85°C, cooled by a cooling plate, and rolled up to obtain a high-toughness prepreg;

[0069] Preparation of halogen-free flame retardant glue: 5 kg of phenolic epoxy resin JF-45, 5 kg of epoxy resin E-51, and 5 kg of epoxy resin E-54 were dissolved and mixed uniformly in a reaction kettle at 100°C, cooled to below 70°C, 5 kg of phosphorus-containing flame retardant phosphate, 5 kg of nitrogen-containing flame retardant melamine, and 0.75 kg of dicyandiamide were added, and continued to stir and mix. After the material was discharged, it was further mixed uniformly by a three-roll mill to obtain a halogen-free flame retardant glue;

[0070] The halogen-free flame retardant adhesive obtained in the previous step is placed between two adhesive rollers of a hot melt adhesive film machine, and the adhesive coating rate is set to 8 m / min. After coating, the film is cooled on a cooling plate and rolled up to obtain a halogen-free flame retardant adhesive film. The thickness of the prepared halogen-free flame retardant adhesive film is about 0.15 mm.

[0071] The high-toughness prepreg was layered in the manner of [+45 / 0 / -45 / 90]5S, and a layer of the halogen-free flame retardant film was inserted into every two layers of prepreg (the halogen-free flame retardant film was only present inside the layers, and the last prepreg layer was not pasted with the film). The high-toughness halogen-free flame retardant composite material was prepared by curing in an autoclave, and the composite material was cut into 150mm×100mm specimens. The post-impact compressive strength (ASTM D7136 / 7137) of the specimen was tested, and the impact energy was 6.67J / mm. The results are shown in Table 1.

[0072] The above-mentioned high-toughness prepreg was layered in the manner of [0]24, and a layer of the above-mentioned halogen-free flame retardant film was added for every two layers of prepreg (the halogen-free flame retardant film was only present inside the layer, and the last prepreg layer was not affixed with the film). The prepreg was cured and formed in an autoclave, and cut into 100mm×6.5mm specimens. The limiting oxygen index (GB / T 8924-2005) was tested. The results are shown in Table 1.

[0073] In this embodiment, the autoclave curing molding process is as follows: evacuate the entire process to 0.098MPa, apply a pressure of 0.6MPa, increase the temperature to 125°C at a heating rate of 1°C / min to 2°C / min and keep warm for 30 minutes, continue to increase the temperature to 185°C and keep warm for 3 hours, cool down to below 60°C at a cooling rate of ≤2°C / min, and release the pressure to exit the tank.

[0074] Example 2

[0075] Preparation of thermoplastic resin glue: 5 kg of epoxy resin E-54, 2 kg of epoxy resin AFG-90, 2 kg of naphthyl epoxy resin EBA-65, 20 kg of polysulfone resin (PS) and 3.6 kg of 4,4-diaminodiphenyl sulfone curing agent were dissolved in N,N-dimethylformamide solvent at room temperature and mixed evenly, and the resin mass concentration was diluted to 50% by adding N,N-dimethylformamide to obtain thermoplastic resin glue;

[0076] The thermoplastic resin glue obtained in the previous step is placed in the glue tank of the prepreg system. Carbon fiber is selected as the reinforcing material. The T700 carbon fiber with a pre-calculated number of axes is passed through the creel device. The prepreg machine pulls the T700 carbon fiber through the above thermoplastic resin glue at a certain pulling rate, so that the resin content of the obtained prepreg is 35%, and is dried in a high-temperature blast drying oven at 145°C to remove the solvent, hot-pressed by a hot pressing roller at 85°C, cooled by a cooling plate, and rolled up to obtain a high-toughness prepreg;

[0077] Preparation of halogen-free flame retardant glue: 5kg of epoxy resin BPNE3501LL and 10kg of epoxy resin E-51 were dissolved and mixed evenly in a reactor at 100°C, cooled to below 70°C, 4kg of phosphorus-containing flame retardant ammonium polyphosphate, 6kg of inorganic metal compound flame retardant aluminum hydroxide and 4.25kg of 4,4-diaminodiphenyl sulfone were added, and stirring and mixing were continued. After the material was discharged, it was further mixed evenly by a three-roll mill to prepare a halogen-free flame retardant glue;

[0078] The halogen-free flame retardant adhesive obtained in the previous step is placed between two adhesive rollers of a hot melt adhesive film machine, and the adhesive coating rate is set to 8 m / min. After coating, the film is cooled on a cooling plate and rolled up to obtain a halogen-free flame retardant adhesive film. The thickness of the prepared halogen-free flame retardant adhesive film is about 0.15 mm.

[0079] The high-toughness prepreg was layered in the manner of [+45 / 0 / -45 / 90]5S, and a layer of the halogen-free flame retardant film was inserted into every two layers of prepreg (the halogen-free flame retardant film was only present inside the layers, and the last prepreg layer was not pasted with the film). The high-toughness halogen-free flame retardant composite material was prepared by curing in an autoclave, and the specimens were cut into 150mm×100mm. The compressive strength after impact (ASTM D 7136 / 7137) was tested, and the impact energy was 6.67J / mm. The results are shown in Table 1.

[0080] The above-mentioned high-toughness prepreg was layered in the manner of [0]24, and a layer of the above-mentioned halogen-free flame retardant film was added for every two layers of prepreg (the halogen-free flame retardant film was only present inside the layer, and the last prepreg layer was not affixed with the film). The prepreg was cured and formed in an autoclave, and cut into 100mm×6.5mm specimens. The limiting oxygen index (GB / T 8924-2005) was tested. The results are shown in Table 1.

[0081] In this embodiment, the autoclave curing molding process is as follows: evacuate the entire process to 0.098MPa, apply a pressure of 0.6MPa, increase the temperature to 125°C at a heating rate of 1°C / min to 2°C / min and keep warm for 30 minutes, continue to increase the temperature to 185°C and keep warm for 3 hours, cool down to below 60°C at a cooling rate of ≤2°C / min, and release the pressure to exit the tank.

[0082] Example 3

[0083] Preparation of thermoplastic resin glue: 5 kg of epoxy resin E-44, 3 kg of epoxy resin EBA-30, 2 kg of epoxy resin AG-80, 20 kg of polyaryletherketone (PEKC) and 2.98 kg of 4,4-diaminodiphenylsulfone curing agent were dissolved in N,N-dimethylformamide solvent at room temperature and mixed evenly, and the resin mass concentration was diluted to 55% by adding N,N-dimethylformamide to obtain thermoplastic resin glue;

[0084] The thermoplastic resin glue obtained in the previous step is placed in the glue tank of the prepreg system. Carbon fiber is selected as the reinforcing material. The T700 carbon fiber with a pre-calculated number of axes is passed through the creel device. The prepreg machine pulls the T700 carbon fiber through the above thermoplastic resin glue at a certain pulling rate, so that the resin content of the obtained prepreg is 38%, and it is dried in a high-temperature blast drying oven at 145°C to remove the solvent, hot-pressed by a hot pressing roller at 85°C, cooled by a cooling plate, and rolled up to obtain a high-toughness prepreg.

[0085] Preparation of halogen-free flame retardant glue: 5kg of epoxy resin E20, 2kg of epoxy resin E-44, 2kg of epoxy resin E-51, and 1kg of epoxy resin E-54 were dissolved and mixed evenly in a reaction kettle at 100°C, cooled to below 70°C, 3kg of phosphorus-containing flame retardant organic hypophosphorous acid, 4kg of nitrogen-containing flame retardant guanidine salt and 2.14kg of 4,4-diaminodiphenyl sulfone were added, and stirring and mixing were continued. After the material was discharged, it was further mixed evenly by a three-roll mill to prepare a halogen-free flame retardant glue;

[0086] The halogen-free flame retardant adhesive obtained in the previous step is placed between two adhesive rollers of a hot melt adhesive film machine, and the adhesive coating rate is set to 8 m / min. After coating, the film is cooled on a cooling plate and rolled up to obtain a halogen-free flame retardant adhesive film. The thickness of the prepared halogen-free flame retardant adhesive film is about 0.15 mm.

[0087] The high-toughness prepreg was layered in the manner of [+45 / 0 / -45 / 90]5S, and a layer of the halogen-free flame retardant film was inserted into every two layers of prepreg (the halogen-free flame retardant film was only present inside the layers, and the last prepreg layer was not pasted with the film). The composite material was prepared by curing in an autoclave and cut into 150mm×100mm specimens. The compressive strength after impact (ASTM D 7136 / 7137) was tested, and the impact energy was 6.67J / mm. The results are shown in Table 1.

[0088] The above-mentioned high-toughness prepreg was layered in the manner of [0]24, and a layer of the above-mentioned halogen-free flame retardant film was added for every two layers of prepreg (the halogen-free flame retardant film was only present inside the layer, and the last prepreg layer was not affixed with the film). The prepreg was cured and formed in an autoclave, and cut into 100mm×6.5mm specimens. The limiting oxygen index (GB / T 8924-2005) was tested. The results are shown in Table 1.

[0089] In this embodiment, the autoclave curing molding process is as follows: evacuate the entire process to 0.098MPa, apply a pressure of 0.6MPa, increase the temperature to 125°C at a heating rate of 1°C / min to 2°C / min and keep warm for 30 minutes, continue to increase the temperature to 185°C and keep warm for 3 hours, cool down to below 60°C at a cooling rate of ≤2°C / min, and release the pressure to exit the tank.

[0090] Table 1 Material test results

[0091] project Test Basis Example 1 Example 2 Example 3 Compression strength after impact / MPa ASTM D 7136 / 7137 328 315 332 Limiting oxygen index / % GB / T 8924-2005 39.6 39.3 37.5

[0092] In the above table, the compression strength after impact is a toughness test index, and the limiting oxygen index is a flame retardancy test index.

[0093] In the prior art, a composite material structure prepared by conventional process is used as a comparative example, the reinforcing material of the comparative example is carbon fiber, the resin material is epoxy resin, which is prepared as a prepreg, and multiple layers of prepreg are stacked, heated and cured to form a composite material. The post-impact compression strength of the composite material can generally only reach about 200MPa, and the limiting oxygen index can only reach about 20%. Comparing Example 1, Example 2 and Example 3, it can be seen that the high-toughness halogen-free flame-retardant composite material prepared by the preparation method of the high-toughness halogen-free flame-retardant composite material provided by the present application has both high toughness and high flame retardant properties. It should be noted that in the prior art, since the flame retardant is generally a powdered particle, the viscosity of the surface of the prepreg to which the flame retardant is added will be reduced. Therefore, when stacking, the prepreg and the prepreg are not high in viscosity, and it is easy to shift, which leads to a decrease in the positioning accuracy of the stacking. In the present embodiment, the high-toughness prepreg does not contain any flame retardant component and has good adhesion. When stacking, the high-toughness prepreg can stick to the high-toughness prepreg or halogen-free flame retardant film adjacent to the threshold, so that the prepreg and the film are not easily displaced after stacking, thereby achieving good positioning of the stacking.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-toughness halogen-free flame-retardant composite material, characterized in that: The following steps are involved: Prepare a thermoplastic resin adhesive, use a prepreg machine to pull the reinforcing material into the thermoplastic resin adhesive, and obtain a high-toughness prepreg after drying and cooling, wherein the mass content of the thermoplastic resin in the high-toughness prepreg is 25% to 80%; Prepare a halogen-free flame retardant adhesive, and shape the halogen-free flame retardant adhesive into a halogen-free flame retardant adhesive film by a hot melt method, wherein the mass content of the halogen-free flame retardant in the halogen-free flame retardant adhesive film is 30% to 80%; Laying the high-toughness prepreg and the halogen-free flame-retardant adhesive film on a laying mold to obtain a high-toughness halogen-free flame-retardant preform; The high-toughness halogen-free flame-retardant preform is cured and formed to obtain a high-toughness halogen-free flame-retardant composite material.

2. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 1, characterized in that: The multiple layers of the high-toughness prepreg and the multiple layers of the halogen-free flame-retardant adhesive film are alternately stacked in the thickness direction.

3. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 2, characterized in that: One or more layers of the halogen-free flame-retardant adhesive film are arranged between two adjacent layers of the high-toughness prepreg; And / or, one or more layers of the high-toughness prepreg are arranged between two adjacent layers of the halogen-free flame-retardant adhesive films.

4. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 1, characterized in that: The thermoplastic resin glue comprises the following components by mass fraction: Thermoplastic resin, 25% to 80%; Epoxy resin, 10% to 75%; Curing agent, 2% to 80%; Curing accelerator, 0-50%.

5. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 4, characterized in that: The thermoplastic resin includes at least one of polysulfone, polyarylethernitrile, polyaryletherketone, polyetheretherketone, thermoplastic polyimide, polyethersulfone, and polycarbonate.

6. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 4, characterized in that: The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin; And / or, the curing agent includes at least one of aliphatic amine curing agents, aromatic amine curing agents, acid anhydrides, imidazoles, and polyamides; And / or, the curing accelerator includes at least one of a substituted urea curing accelerator, a boron trifluoride amine complex curing accelerator, a triphenylphosphine and its salt curing accelerator, and a tertiary amine and its salt curing accelerator.

7. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 1, characterized in that: The reinforcing material includes at least one of carbon fiber and fabric thereof, glass fiber and fabric thereof, aramid fiber and fabric thereof, basalt fiber and fabric thereof, and aramid fiber and fabric thereof.

8. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 1, characterized in that: The halogen-free flame retardant adhesive comprises the following components by mass fraction: Halogen-free flame retardant, 30% to 80%; Epoxy resin, 20% to 70%; Curing agent, 2% to 80%; Curing accelerator, 0-50%; The type of the curing agent in the halogen-free flame retardant glue is consistent with the type of the curing agent in the thermoplastic resin glue solution, and the type of the curing agent accelerator in the halogen-free flame retardant glue is consistent with the type of the curing agent accelerator in the thermoplastic resin glue solution.

9. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 8, characterized in that: The halogen-free flame retardant includes at least one of a phosphorus-based flame retardant, a nitrogen-based flame retardant, a silicon-based flame retardant, and an inorganic metal compound flame retardant.

10. The method for preparing the high-toughness halogen-free flame-retardant composite material according to claim 8, characterized in that: The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, aminophenol trifunctional epoxy resin, amino tetrafunctional epoxy resin, bisphenol F epoxy resin, and naphthyl epoxy resin; And / or, the curing agent includes at least one of aliphatic amine curing agents, aromatic amine curing agents, acid anhydrides, imidazoles, and polyamides; And / or, the curing accelerator includes at least one of a substituted urea curing accelerator, a boron trifluoride amine complex curing accelerator, a triphenylphosphine and its salt curing accelerator, and a tertiary amine and its salt curing accelerator.